INTERNALISASI NILAI KARAKTER ANAK MELALUI PENGULANGAN SURAT AL-FATIHAH: SEBUAH SINTESIS KOMPREHENSIF BERDASARKAN NEUROSAINS, PSIKOLOGI PENDIDIKAN, DAN TEOLOGI ISLAM - Isrun Abdurahman; Rohman Pranoto; Agus Salim; Rizaldy Alpiansyah; Irfan Alkhotiri (Mutamayyiz: Journal of Islamic Studies, 2026)
This study is a Systematic Literature Review (SLR) that aims to analyze and synthesize findings from various studies related to the internalization of children's character values through the repetition of Surah Al-Fatihah in prayer, as well as to identify patterns, consensus, and existing research gaps.1 The synthesis results show that Surah Al-Fatihah contains comprehensive character values, encompassing spiritual-moral, social-leadership, and educational aspects.1 The repetition of reciting Al-Fatihah acts as a mechanism for internalizing values through the processes of neuroplasticity and habit formation.1 This paper bridges Islamic theological studies with recent findings in cognitive psychology and neurobiology to provide an operational foundation for children's character education in the modern era.